The Books’ Road in the Age of Digitization - Krieger, Janina (Springer Berlin Heidelberg, 2023)
The problem and its background – Approach & methods of analysis – The study of readers:
10.1007/978-3-662-66683-8
Keywords: Literature.; Mass media and culture.; Literature and technology.; Mass media and literature.